Laboratory Imaginative Work Information System With Waterfall Method (Case Unas Artificial Intelligence Laboratory) - Rima Tamara Aldisa (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
Data processing is a routine and important requirement for companies, organizations that must be prepared and maintained properly, accurately. Therefore, it is necessary to create a system to be able to manage this data properly, namely with computers or laptops for data processing, storage and analysis of the results obtained. fast and realtime. Artificial Intelligence Computer Laboratory, Faculty of Communication and Information Technology, National University designed an imaginative information system using the waterfall method as the initial flow or first process flow to design or create a system as a means to carry out activities that aim to provide information, knowledge and also make it easier for users to knowing what results have been created, created, designed, developed, owned by the Artificial Intelligence laboratory. The results of this design or system will be based on the website.